DEVELOPMENT OF SMES PROMOTION MEDIA THROUGH SECI-BASED DIGITAL CATALOG IN BANDUNG REGENCY - Achmad, Fandi; Anggana, Hilman Dwi; Rumanti, Augustina Asih; Rial, Muhamad Daffa; Suryaneda, Azzahra Putri; Sena, Muhammad Avin; Aditya, Reza (Politeknik META Industri Cikarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic sector in the economy of Bandung Regency, playing a vital role in job creation and local economic growth. However, many MSME actors still face challenges in promotion, particularly in presenting product information in a professional and systematic manner. This study aims to design a catalog for MSMEs that serves not only as a promotional tool but also as a medium for documentation and knowledge transfer, using the SECI method (Socialization, Externalization, Combination, Internalization). The SECI approach is utilized to manage and convert tacit knowledge from MSME actors into explicit knowledge documented in the form of a catalog. Data were collected through interviews, field observations, and literature reviews to identify the potentials and needs of local businesses. The result is a catalog design in both print and digital formats, containing MSME profiles, product descriptions, contact information, and local visual elements such as Kina batik. Each stage of the SECI model was applied systematically to ensure the catalog authentically represents the characteristics of the MSMEs and is easily understood by consumers. Validation results indicate that the catalog functions effectively as a collaborative promotional tool that is informative and cost-efficient. From a cost perspective, joint catalog promotion can reduce expenses by up to 93.81% compared to individual efforts. Future research recommends developing the catalog into an interactive digital version, such as an application or website, to expand market reach and enhance the sustainability of the MSME ecosystem in Bandung RegencyKeywords: MSMEs, SECI method, catalog, promotion, knowledge transfer